2004
DOI: 10.1097/01.ccm.0000143118.41100.14
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial therapy for patients with severe sepsis and septic shock: An evidence-based review

Abstract: Since the prompt institution of therapy that is active against the causative pathogen is one of the most important predictors of outcome, clinicians must establish a system for rapid administration of a rationally chosen drug or combination of drugs when sepsis or septic shock is suspected. The expanding number of antibacterial, antifungal, and antiviral agents available provides opportunities for effective empiric and specific therapy. However, to minimize the promotion of antimicrobial resistance and cost an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
88
0
12

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(101 citation statements)
references
References 195 publications
1
88
0
12
Order By: Relevance
“…Bacteremia is detected in approximately 30-50% of cases of severe sepsis and septic shock [20,21]. Kamei et al [11] reported that a positive blood culture is a risk factor for septic shock in patients with obstructive pyelonephritis (OR, 9.11), and bacteremia in severe acute pyelonephritis showed significant association with a hospital stay longer than 14 days (OR, 3.71) [12].…”
Section: ) Bacteremiamentioning
confidence: 99%
“…Bacteremia is detected in approximately 30-50% of cases of severe sepsis and septic shock [20,21]. Kamei et al [11] reported that a positive blood culture is a risk factor for septic shock in patients with obstructive pyelonephritis (OR, 9.11), and bacteremia in severe acute pyelonephritis showed significant association with a hospital stay longer than 14 days (OR, 3.71) [12].…”
Section: ) Bacteremiamentioning
confidence: 99%
“…El tratamiento antibiótico es una de las bases fundamentales del tratamiento de la sepsis 64 , su cumplimiento guarda estrecha relación con el pronóstico del paciente 4,65 . En un trabajo clásico, Kumar et al 4 , demostraron en población adulta un aumento de la mortalidad en un 7% por cada hora transcurrida sin uso de antibiótico.…”
Section: Inicio De Antibióticosunclassified
“…These conditions are generally associated with multiple organ failure as final outcome (1)(2)(3)(4)(5). Over the past 30 years, the worldwide incidence of sepsis has increased by 13.7% per year (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…These conditions are generally associated with multiple organ failure as final outcome (1)(2)(3)(4)(5). Over the past 30 years, the worldwide incidence of sepsis has increased by 13.7% per year (1)(2)(3)(4)(5). It is therefore estimated that more than 18 million people suffer from sepsis each year and more than five million of them die (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation